The Instability of Governments and the Instability of Controls on Funds Transfers by Multinational Enterprises: Implications for Political Risk Analysis - Brewer, Thomas L. (Journal of International Business Studies, 1983)
This article represents a departure from previous empirical political risk studies: it explicitly focuses on the association between specific governmental policy changes and other forms and political instability. A cross-national study of 115 countries finds positive but weak relationships between policy instability and other indicators of political instability. The findings indicate the need to reconsider common assumptions about political risks.